Republic of Moldova : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2008)
Statistical details of gross domestic product by expenditure and sector, industrial production, agricultural and industrial production indices, agricultural production by sector, nominal wages by sector, employment by sector, unemployment, unpaid leave, and part-time employment, central government operations, local government operations, accounts of the national bank, monetary survey, composition and direction of trade are listed. The appendix includes basic data such as area, population, life expectancy for both male and female, infant mortality rate, hospital beds, and primary and secondary education rates.